2008
DOI: 10.1002/jemt.20605
|View full text |Cite
|
Sign up to set email alerts
|

Histology and ultrastructure of Aedes albopictus larval midgut infected with Bacillus thuringiensis var. israelensis

Abstract: Histological and ultrastrucutural alterations in the midgut of Aedes albopictus larvae infected with Bacillus thuringiensis var. israelensis (Bti) were observed by light and transmission electron microscopy (TEM). Two formulations of Bti were used: granulated and powder, with 0.2% active ingredient in 90 larvae of Ae. albopictus distributed in three containers containing 30 larvae each (one control group and two test groups). The midgut epithelium of the control group presented flattened and elongated cells wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
7
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 22 publications
4
7
0
Order By: Relevance
“…5 a). The results are in accordance with previous reports 61 . The toxicity of the plant essential oil (EO) as an insecticide mainly depends on penetration rate of EO into the insect body, their interaction with specific target enzymes and the detoxification ability of the mosquito at each developmental stage 62 .…”
Section: Resultssupporting
confidence: 94%
See 2 more Smart Citations
“…5 a). The results are in accordance with previous reports 61 . The toxicity of the plant essential oil (EO) as an insecticide mainly depends on penetration rate of EO into the insect body, their interaction with specific target enzymes and the detoxification ability of the mosquito at each developmental stage 62 .…”
Section: Resultssupporting
confidence: 94%
“…Some earlier researchers have also reported the morphological aberrations induced by nano based botanical pesticide on mosquito larvae 11 , 63 . The comparatively severe damage occurred in the larval midgut cells treated with nano-CWO may attributed to the remarkable feature of nanoparticles; larger surface and smaller size, which can promote easy penetration into the larval body and disturb their normal cycle of life by interrupting the intake of feed, cell division and breathing, the statement is supported by previous literature 61 , 64 .
Figure 5 Cytomorphology of midgut of larva ( A ) Control ( B ) CWO nanocapsules, magnification 40×.
…”
Section: Resultssupporting
confidence: 62%
See 1 more Smart Citation
“…israelensis (Bti) were observed by Silva et al (2008). After Bti ingestion, the intestinal cells showed a disorganization of the basal processes, dilatation and fragmentation of the rough endoplasmic reticulum, with intense cytoplasmic vacuolization.…”
Section: Results Of Histological Studymentioning
confidence: 99%
“…Similar results as ours were obtained in histological analyses of Culex nigripalpus larvae infected by Bacillus thuringiensis medellin (Cry11Bb) [36] and in intestinal cells of larvae of Aedes albopictus infected with B. thuringiensis var. israelensis (Bti) [37]. The authors reported as signs of infection, the presence of rounded cells, cytoplasm with granules, clear or absent nucleus and extensive cytoplasmic vacuolization of epithelial cells of the mesentery of these larvae.…”
Section: Discussionmentioning
confidence: 99%